Population aging and the possibility of a middle-income trap in Asia - Joonkyung Ha; Sang-Hyop Lee (Asian Development Bank (ADB), 2018)
We present three conditions for a demography-driven middle-income trap and show that many economies in East, South, and Southeast Asia satisfy all of them. The conditions are (1) support ratio - the ratio of workers to consumers - matters for economic growth, (2) economic development accompanies more investment in human capital and lower fertility due to the quantity-quality tradeoff, and (3) current low level of fertility corresponds to too low support ratios for keeping up with the frontier economies in the long run. The panel analyses for 178 countries, among which 30 are ADB developing member economies, show that (i) and (ii) are satisfied for Asia with higher elasticity than others. As for (iii), we set up a dynamic model for simulations, showing that about two-thirds of ADB members have unsustainable level of support ratios, implying possibilities of a middle-income trap due to demographic headwinds in the future.
Keywords: J11; O11; O53; 330; demography; fertility; middle-income trap; national transfer accounts; support ratio